equation for parabola is
y = a ( x - h ) ^2 + k where (h,k) is the vertex of the parabola.
Given: vertex (-4, -1) h = -4; k = -1
y = a (x - (-4))^2 + (-1)
y = a ( x + 4)^2 - 1 plug in the values given for x and y. y-value is 0 and x-value is 2
0 = a (2 + 4)^2 -1
0 = a (6)^2 -1 square 6
0 = a 36 - 1 add 1 to both sides to isolate the a
1 = 36 a divide both sides by 36 to isolate the a
1/36 = a the coefficient.
i think you might have typed a number incorrectly if those are your answer choices. Maybe the step by step process can still help you with your correct numbers. :-)